WASTE MANAGEMENT SYSTEMS AND MECHANISMS OF THAILAND AND OVERSEAS - Wongchummali, Piyarat; Pampasit, Rudklaw (PEOPLE: International Journal of Social Sciences, 2017)
This article purposed to review the systems and mechanisms of waste management in Thailand and overseas for leading to a solution of waste management in a proper way conforming to a current situation of waste in areas. This was a documentary study using an academic document and basic information from the involving departments about waste management. The finding found that the waste management of overseas following the framework of Zero Waste for reducing the amount of waste into least then disposing by proper technology with 3Rs Reduce Reuse and Recycle and Polluter Pays Principle: PPP which a mechanism for protecting the waste systematical since production, using, and consuming. These made the overseas solved the waste problem efficiently.The finding suggested that 1) the policy planning should cover the involved activities with the waste management 2) law or tax enforcement 3) promoting to do a research and developing the technology for seriously solving the waste problem in country and 4) promoting the Local Administration Organizations for cooperation with enterprise in order to manage the waste following the environmental standard in roles, pattern, and directing for efficiency.